Autism spectrum disorders in sub-Saharan Africa - Abubakar, A; Ssewanyana, D; de Vries, P; Newton, C (Elsevier, 2016)
Autism spectrum disorder (ASD) is one of the most prevalent neurodevelopmental disorders in high-income countries, but little is known about it in Africa or other low- and middle-income countries1,2. A recent review of the global prevalence of autism did not identify any data from sub-Saharan Africa (SSA)3, even though this region has a population of nearly 1 billion, of whom 40% are children aged less than 14 years. To date the public health emphasis in SSA has been on communicable conditions such as HIV, malaria and tuberculosis4. However, with the reduction in childhood mortality in recent decades, non-communicable diseases (in particular neurodevelopmental disorders) are likely to become a greater burden on the health system of these countries4. Given these circumstances there is an urgent need for studies on ASD and other neurodevelopmental disorders in Africa.